Chaired panel "Dialogue As The Embodiment of Love" - Richard James Talbot (2020)
A public panel chaired by Richard Talbot. A discussion following a staging of the complete trilogy Open Dialogue, Performance and Mental Health Care as part of Ridiculusmus' "Dialogue As The Embodiment of Love" trilogy of performances. The panel features Drs Jon Haynes and David Woods (Ridiculusmus), Anni Haase and Mia Kurti, Open Dialogue Supervisors and Trainers with Polyclinic in Tornio Western Lapland, Andrew Ravenscroft Professor of Education, University of East London, Dr Maria Grazia Turri, Lecturer in Creative Arts and Mental Health, Queen Mary, University of London. Chaired by Dr Richard Talbot, Senior Lecturer in Performance, University of Salford. https://soundcloud.com/richard-talbot-318441855/dialogue-as-the-embodiment-of-love-panel-discussion Recorded at Battersea Arts Centre on 25th May 2019. For details on the panel: tinyurl.com/y4gsylr8